Effects of malting conditions on enzyme activities, chemical, and bioactive compounds of sorghum starchy products as raw material for brewery. (2nd June 2016) - Garzón, Antonela Guadalupe; Torres, Roberto Luis; Drago, Silvina Rosa
Abstract : Two cultivars of sorghum (red, RS and white, WS) were germinated at 25 or 30°C for 1, 2, or 3 days and were evaluated regarding enzyme activities (diastatic power: DP, β‐amylase), chemical compounds (total starch, damaged starch, glucose, free amino acid), and bioactive compounds (free phenolic compounds: FPC and γ‐aminobutyric acid:GABA). For WS and RS (on third germination day at 30°C), DP was 11.3 ± 1.4 and 10.8 ± 1.3 °DP, β‐amylase activity: 33.0 ± 0.9 and 71.1 ± 0.7 UBetamyl/g d.b., respectively, while at 25°C, DP was 6.1 ± 0.7 and 18.0 ± 1.1 °DP, β‐amylase activity: 9.3 ± 0.5 and 57.8 ± 0.3 UBetamyl/g d.b., respectively. Starch degradation, free amino acids, and free glucose content increased during germination, and depended on cultivar, germination time and temperature. The hydrolysis of the protein matrix influenced the release of starch granules, which were more accessible to amylolytic action. FPC and GABA levels were higher after grain germination and depended on sorghum cultivar and germination temperature. Germination at 30°C for 3 days represented the most suitable conditions for obtaining good bio‐functional sorghum malt.